COMPARISON OF ADVERB PHRASES IN ENGLISH AND UZBEK LANGUAGE (Journal of Science-Innovative Research in Uzbekistan, 2024)
This study explores the linguistic structures and usage of adverb phrases in both English and Uzbek languages, focusing on their similarities and differences in formation, function, and placement within sentences. English adverbial phrases are characterized by their flexibility in positioning and can modify verbs, adjectives, or other adverbs to convey nuances of manner, time, place, or degree. These phrases often consist of an adverb coupled with additional modifying words, allowing for a broad expressive range. Conversely, in the Uzbek language, adverbial phrases predominantly follow the word they modify, reflecting a more rigid syntactical structure typical of Turkic languages. The formation of Uzbek adverbial phrases frequently utilizes suffixation and other morphological methods, distinct from the English preference for prepositional and adverb-adjective constructions. This comparative analysis sheds light on the intricate ways in which adverbial phrases enrich linguistic expression and contribute to the depth of meaning in both languages, highlighting the importance of syntactic understanding in multilingual contexts. The findings aim to contribute to the fields of comparative linguistics and language education by providing insights into the cross-linguistic variations in adverbial usage, thereby facilitating more effective language learning and translation strategies.